Beginning Music Teacher Mentor Practices: Reflections on the Past and Suggestions for the Future. (February 2015) - Conway, Colleen
The purpose of this inquiry was to examine the current reflections of 13 experienced teachers on their past perceptions of mentoring as documented by Conway (2003a). Participants read the 2003 study and examined all data collected in 1999-2000, including journals, two questionnaires, individual interviews, focus group interviews, mentor interviews, and principal interviews. They then wrote an e-mail reflection on that reading and participated in an individual interview regarding their current perceptions on mentoring beginning music teachers. I sought to understand whether findings represented in the 2003 study were perceived to be still relevant today. In addition, I sought to uncover additional insights regarding mentoring that these participants could offer. Findings are presented in the following categories: (a) mentoring can be valuable for the mentor; (b) disagreement regarding who should mentor; and (c) new teachers must be proactive in finding answers to questions. Themes consistent with the 2003 findings include (a) a lack of consistency in mentor programs and teacher perceptions of value, (b) curricular concerns, (c) music teachers need music mentors, and (d) time for mentor–mentee interaction. Connections are made to past research, and suggestions for future research and mentoring practice are provided.